The waist-to-height ratio is a good predictor for insulin resistance in women with polycystic ovary syndrome - Zhu, Mengyi; Wang, Kaiyue; Feng, Jiaxing; Liu, Yang; Guan, Muxin; Wang, Yu; Wu, Xiaoke (Frontiers in Endocrinology, 2024)
Objective: This study aimed to explore the role of waist-to-height ratio (WHtR) in assessing insulin resistance (IR) in polycystic ovary syndrome (PCOS) patients.We enrolled 882 PCOS-afflicted females in a cross-sectional analysis to evaluate the association of WHtR with IR. Their demographic characteristics, anthropometric parameters, and fasting blood samples were collected and measured. Moreover, IR was evaluated by homeostatic model assessment of insulin resistance (HOMA-IR). We estimated the relationship between WHtR and IR and the cut-off thresholds of WHtR for IR using multivariable linear regression and logistic regression models, respectively.The prevalence rate of IR was 51.9%. The PCOS patients with IR displayed significantly enhanced values of body mass index (BMI), waist circumference (WC), WHtR, systolic blood pressure (SBP), diastolic blood pressure (DBP), free androgen index (FAI), HOMA-IR, total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and apolipoprotein B (ApoB).However, PCOS patients with IR showed a reduction in estradiol (E2), luteinizing hormone (LH), LH/FSH ratio, sex hormone binding globulin (SHBG), and high-density lipoprotein (HDL-C) values than those without IR. Moreover, BMI (log-transformed), WC, and HOMA-IR (log-transformed) were positively correlated with WHtR. When adjusting for potential confounding variables, WHtR was significantly associated with HOMA-IR (log-transformed), with a standardized regression coefficient of 0.271. Furthermore, WHtR was associated significantly with an increased risk of IR, with the adjusted odds ratio (OR) of 3.15 (WHtR multiplied by 10). Additionally, WHtR helped to identify IR in PCOS women with an optimal cut-off point of 0.519 (Youden index = 0.433).WHtR has a positive association with IR in women with PCOS.Hence, we suggest WHtR as a simple, practical, and reliable anthropometric measure to be used to predict the risk of IR in PCOS patients.